The Use of Pine Cone Extract in the Production of Albumen Curd - Chatinyan, Nara; Stepanayan, Naira; Mezhlumyan, Anahit (ՀԱԱՀ հիմնադրամ)
Due to a lack of protein in the human diet, dairy products made from milk proteins have increased in production. The proposed new product was made from cheese whey and curds. The main ingredients were whey proteins and pine cone extract as a natural additive. The relevance of making albumen curd with vegetable extract is scientifically and experimentally justified. Based on this study, the optimal dose of pine cone extract was determined which results in imparting a distinctive taste and aroma characteristic of pine cone, improving the chemical composition, and extending the product’s shelf life.
Keywords: Food Science and Technology